Aminophenol-Decorated Gold Nanoparticles for Curing Bacterial Infections - Wang, Le; Zheng, Wenfu; Li, Sixiang; Zhong, Leni; Jiang, Xingyu (Nano letters, 2022)
Nanomaterials usually kill bacteria via multiple mechanisms which are not explicit to the same degree as those of conventional antibiotics. This situation may hinder the development of novel nanoscale antibiotics. Here, we present aminophenol (AP) to modify gold nanoparticles (AP_Au NPs) which show a broad antibacterial spectrum and potent antibacterial effects against multidrug-resistant (MDR) bacteria with clear antibacterial mechanisms. AP_Au NPs can not only damage bacterial cell walls but also bind to the 16S rRNA to block bacterial protein synthesis. Moreover, AP_Au NPs show excellent performance in curing abdominal bacterial infections in an in vivo model. AP_Au NPs thus have the potential to become a novel antibacterial agent for clinical applications.